Study guide to accompany : Seitz, Nelson, Harcrow, Economics of resources, agriculture, and food - Johnson, Marvin B.; Johnson, Tera L. (New York : McGraw-Hill, 1994)
This book is divided into five parts: Economic scope, organization, and problems os agriculture; Microeconomic concepts; Markets; Macroeconomic relationships; and Public policy and agriculture.
Keywords: Agriculture; Economics; Agriculture -- Economic aspects; Agricultural industries; Agriculture and state